A numerical study of isotopic evolution of a seasonal snowpack and its meltwater by melting rates - Lee, Jeonghoon (Geosciences journal (Seoul, Korea), 2014)
Understanding an isotopic evolution of a snowpack and its meltwater is crucial for both past and current climate and hydrological studies because the snowmelt is a substantial component of groundwater and surface runoff in temperate regions. To better understand the isotopic evolution of a snowpack, this study investigated the stable isotopic compositions of a snowpack and its melt using a physically-based one-dimensional model with different melting rates, which are dependent upon air temperature, amount of short-wave radiation that snow absorbed and aspect differences (north facing vs. south facing). The low melting rate produces a more curved and relatively larger isotopic differences between the earlier and later meltwater. On the other hand, the high melting rate yields a less curved isotopic trend and a smaller isotopic range. Low melting rate tends to make the snowpack isotopically heavier in both homogeneous and heterogeneous snowpack. Changes in melting rate at the surface were accompanied by the changes of both percolation velocity of liquid water and contact time between liquid water and snow (or ice). Therefore, the differences between isotopic values of the snowpack and meltwater decreases as the melting rate increases. Dependence of isotopic evolution of a snowpack and its meltwater on melting rate potentially important for studying snowmelt hydrology and ice cores for paleoclimate.